How Do Personality Traits Influence the Behavioral Intentions of Gen-Z Tourists? - Alexander Joseph Ibnu Wibowo (Tržište, 2023)
Purpose – This paper examined the influence of tourists’ personality traits, the perception of tourist destinations, and attitudes toward a destination on the behavioral intention of members of Generation Z in Indonesia during the COVID-19 pandemic. Design/Methodology/Approach – A total of 682 responses were collected through an online survey using the convenience sampling method. After removing the input from respondents who did not meet the criteria and outliers, 619 responses were analyzed. Furthermore, six hypotheses were tested using structural equation modeling. Findings and Implications – The results affirm that personality traits influence the perception of tourist destinations and attitudes toward a destination. This perception significantly affects attitude and behavioral intention. Likewise, attitude toward a destination determines behavioral intention considerably. Limitations – Respondents were selected using the nonprobability sampling method, so the findings are not representative of the entire tourist population worldwide. Therefore, the generalizability of the conclusions is likely limited. Originality – This research study contributes to expanding the existing knowledge about how personality traits, perception, and attitude are combined to increase behavioral intention in the case of tourism. It is a step in describing and deepening the examination of personality traits and their outcomes in the context of emerging countries. The findings are expected to help confirm the importance of using market segmentation as a marketing strategy and shape travel advertisements that focus on personality traits as well as the attitudes and behaviors that are relevant to personality traits.